The Importance of Developing Social Competences of Future Teachers In The Process of Educational Transformation - Bahodirovna, Hojiyeva (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2025)
The article examines the issue of developing social competencies of future teachers. The concept of social competence, its content and significance in the education system are considered in detail. It also describes the transformation of the educational process, that is, the process of acquiring new types of competencies by a teacher, including the development of social and communicative potential. The effectiveness of forming social competencies of future teachers through modern pedagogical methods, such as role-playing, problem situations, trainings and seminars, and innovative and interactive approaches is analyzed. Social competencies help students develop not only communication and social integration skills, but also such qualities as intercultural tolerance, empathy, teamwork and responsibility.